Movement of Free-Ranging Koalas in Response to Male Vocalisation Playbacks - Alex Zijian Jiang; Peter Murray; Clive Phillips; Andrew Tribe; William Ellis (Animals, 2022)
Effective conservation strategies rely on knowledge of seasonal and social drivers of animal behaviour. Koalas are generally solitary and their social arrangement appears to rely on vocal and chemical signalling. Male koala vocalisations, known as bellows, are believed to be closely related to their breeding behaviour. Previous research suggests that oestrous female koalas use bellows to locate unique males to mate with, and that males can similarly use bellows to evaluate the physical attributes of their peers. We tested the behavioural responses of 20 free ranging koalas to bellow recordings collected from small (<6 kg) and large (>8.5 kg) adult male koalas. Individual koala movement was reported by hourly-uploaded GPS coordinates. We report evidence of intra-male competition, with adult males approaching bellow playbacks, particularly those from small-sized males. In contrast, males under three years of age were averse to the playbacks. No patterns in the response of females were detected. Our results provide the strongest evidence yet that bellows are primarily a means by which males occupy and control space during the breeding season. Future studies are required to see if female response to bellows depends on their reproductive status.